2019
DOI: 10.4111/icu.2019.60.5.359
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with low-energy shock wave alleviates pain in an animal model of uroplakin 3A-induced autoimmune interstitial cystitis/painful bladder syndrome

Abstract: Purpose To investigate whether treatment with low-energy shock wave (LESW) alleviates pain and bladder dysfunction in a mouse model of uroplakin 3A (UPK3A)-induced interstitial cystitis/painful bladder syndrome (IC/PBS). Materials and Methods Forty female BALB/c mice were divided into four groups (n=10/group): Sham, Sham+LESW, UPK3A, and UPK3A+LESW. At 6 weeks of age, mice were injected with an emulsion containing water and complete Freund's adjuvant with (UPK3A and UPK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Enzyme-linked immunosorbent assays (ELISA). For muTNF-α quantitation by ELISA, serum and PBS brain homogenates were diluted with the ELISA sample buffer and sample duplicates were run on specific sandwich colorimetric ELISAs (Biolegend) according to the manufacturer's protocol as previously described 64 . Optical (2020) 10:8670 | https://doi.org/10.1038/s41598-020-65378-2 www.nature.com/scientificreports www.nature.com/scientificreports/ densities at 450 nm of each well were read on a microplate reader (ELx800, BioTek Instruments, Winooski, VT, USA), and sample TNF-α concentrations were determined by comparison with the respective standard curves using the Gen5 software (BioTek Instruments).…”
Section: Methodsmentioning
confidence: 99%
“…Enzyme-linked immunosorbent assays (ELISA). For muTNF-α quantitation by ELISA, serum and PBS brain homogenates were diluted with the ELISA sample buffer and sample duplicates were run on specific sandwich colorimetric ELISAs (Biolegend) according to the manufacturer's protocol as previously described 64 . Optical (2020) 10:8670 | https://doi.org/10.1038/s41598-020-65378-2 www.nature.com/scientificreports www.nature.com/scientificreports/ densities at 450 nm of each well were read on a microplate reader (ELx800, BioTek Instruments, Winooski, VT, USA), and sample TNF-α concentrations were determined by comparison with the respective standard curves using the Gen5 software (BioTek Instruments).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Li et al. reported that local treatment with low‐energy shock wave improved bladder inflammation and pain, and reduced levels of TNF‐α and NGF in bladder and serum in the EAC mice 119 …”
Section: Animal Modelsmentioning
confidence: 99%
“…Several preclinical studies have identified molecular changes induced by Li-ESWT in the bladder. In a uroplakin-induced bladder pain model, Li-ESWT significantly decreased the expression and secretion of local and systemic inflammatory markers, including TNF-α and nerve growth factor (NGF), which were increased after uroplakin 3A immunization [7]. In a rat model of cryoinjury-induced DU, Li-ESWT improved the expression of TGF-β1 and vascular endothelial growth factor (VEGF) as well as of Ki-67 [4].…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 99%
“…Increasing preclinical evidence supports the role of low intensity extracorporeal shockwave therapy (Li-ESWT) in the treatment of non-infectious cystitis and detrusor underactivity. In a variety of animal models including cyclophosphamide-induced cystitis, radiation cystitis, uroplakin-induced autoimmune interstitial cystitis, cryoinjury-induced detrusor underactivity, and diabetic underactive bladder, treatment with Li-ESWT was found to improve bladder dysfunction and pain, reduce the inflammatory response, ameliorate muscle contractility and bladder morphology [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%